Apixaban vs. standard of care after transcatheter aortic valve implantation: the ATLANTIS trial. (18th May 2022) - Collet, Jean Philippe; Van Belle, Eric; Thiele, Holger; Berti, Sergio; Lhermusier, Thibault; Manigold, Thibault; Neumann, Franz Josef; Gilard, Martine; Attias, David; Beygui, Farzin; Cequier, Angel; Alfonso, Fernando; et al.
Abstract: Aims: The respective roles of oral anticoagulation or antiplatelet therapy following transcatheter aortic valve implantation (TAVI) remain debated. ATLANTIS is an international, randomized, open-label, superiority trial comparing apixaban to the standard of care. Methods and results: After successful TAVI, 1500 patients were randomized (1:1) to receive apixaban 5 mg (2.5 mg if impaired renal function or concomitant antiplatelet therapy) ( n  = 749) twice daily, or standard of care ( n  = 751). Randomization was stratified by the need for chronic anticoagulation therapy. Standard-of-care patients received a vitamin K antagonist (VKA) (Stratum 1) or antiplatelet therapy (Stratum 2) if there was an indication for anticoagulation or not, respectively. The primary endpoint was the composite of death, myocardial infarction, stroke or transient ischaemic attack, systemic embolism, intracardiac or bioprosthesis thrombosis, deep vein thrombosis or pulmonary embolism, and life-threatening, disabling, or major bleeding over 1-year follow-up. The primary safety endpoint was major, disabling, or life-threatening bleeding. The primary outcome occurred in 138 (18.4%) and 151 (20.1%) patients receiving apixaban or standard of care, respectively [hazard ratio (HR) 0.92; 95% confidence interval (CI) 0.73–1.16] and there was no evidence of interaction between treatment and stratum ( P interaction  = 0.57). The primary safety endpoint was similar in both groups (HR 1.02; 95% CI 0.72–1.44). In Stratum 1 ( n  = 451), an exploratory analysis showed no difference for all endpoints between apixaban and VKA. In Stratum 2 ( n  = 1049), the primary outcome and primary safety endpoint did not differ, but obstructive valve thrombosis was reduced with apixaban vs. antiplatelet therapy (HR 0.19; 95% CI 0.08–0.46), while a signal of higher non-cardiovascular mortality was observed with apixaban. Conclusion: After TAVI, apixaban was not superior to the standard of care, irrespective of an indication for oral anticoagulation. Structured Graphical Abstract: Structured Graphical Abstract Primary endpoint and primary safety analysis of the ATLANTIS trial.